Modern biomarkers as key tools in the early diagnosis and monitoring of Alzheimer’s disease progression - Strużek, Konrad; Karamus, Kornelia; Rejmak, Rafał; Borowska-Łygan, Martyna; Urban, Wojciech; Tomaszewski, Jakub; Gryc, Anna; Lipiec, Jakub; Grudzień, Monika (Journal of Education, Health and Sport, 2025)
Advances in the understanding of Alzheimer’s disease (AD) pathophysiology, along with the development of neuroimaging and biomarker analysis, have enabled the detection of neurodegenerative changes even before clinical symptoms appear. This article explores the evolution of AD diagnostic criteria, with a particular focus on the pivotal role of cerebrospinal fluid biomarkers (Aβ42, t-tau, p-tau) and brain imaging techniques (MRI, PET). The A/T/N classification system and the concept of compensatory brain mechanisms are also discussed, emphasizing their relevance in early disease detection. The modern diagnostic approach, introduced by the Dubois criteria and further developed by the NIA-AA framework, allows for the identification of AD in its preclinical phase. The presence of biomarker abnormalities in asymptomatic individuals suggests a long latent period and the activation of neuroplastic compensatory processes that may delay symptom onset. The integration of biomarkers has significantly improved diagnostic accuracy, enhanced clinical trial participant selection, and enabled more precise disease monitoring. Despite these advances, effective treatments to halt or reverse disease progression remain elusive, highlighting the urgent need for further research into compensatory mechanisms, individual variability, and early therapeutic strategies.